1989
DOI: 10.1111/j.1600-0722.1989.tb01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline as a marker in hard tissue research: effects on enamel formation in rat maxillary incisors

Abstract: Abstract— Tetracycline in low dose is often used as a marker in hard tissue research. A low dose effect on enamel formation has never been proven despite well known toxic reactions in enamel after higher doses. The purpose of the investigation was to evaluate enamel formation in maxillary incisors of rats given a single low dose of a tetracycline with low toxicity, commonly used in research. Eight young rats received an intraperiotonal injection of 2 mg oxytetracycline per 100 g. The rats were terminated after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…This compares with the studies by Fatani and Raja [8] who reported a rate of 0.015 mm/day, using radioautographs. The growth rate of the teeth in this study was also seen to be less in the presence of tetracycline which compares with Ranggard [11] who reported that even a single low dose of tetracycline (2 mg oxytetracycline per 100 g) caused a disturbance in normal amelogenesis in the rat incisor. The question then is "How does this affect the interpretation of the results when tetracycline is used as a histological marker for other studies?"…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…This compares with the studies by Fatani and Raja [8] who reported a rate of 0.015 mm/day, using radioautographs. The growth rate of the teeth in this study was also seen to be less in the presence of tetracycline which compares with Ranggard [11] who reported that even a single low dose of tetracycline (2 mg oxytetracycline per 100 g) caused a disturbance in normal amelogenesis in the rat incisor. The question then is "How does this affect the interpretation of the results when tetracycline is used as a histological marker for other studies?"…”
Section: Discussionsupporting
confidence: 44%
“…Fatani and Raja [27], using radioautographs, measured the thickness of dentine laid down per day as 0.015 mm. It is clear that the growth rate of teeth is effected by many factors, including age of animal [28,31], the physical properties of the diet [33], and medications [11]. In this study the mean growth of teeth was 0.010 mm/day during the period of tetracycline administration and 0.016 mm/day when no tetracycline was being administered.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations